Neonatal piglet survival: impact of sow nutrition around parturition on fetal glycogen deposition and production and composition of colostrum and transient milk. (25th April 2014) - Theil, P. K.; Lauridsen, C.; Quesnel, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Piglet survival is a major problem, especially during the first 3 days after birth. Piglets are born deficient of energy, but at the same time they have a very high energy requirement because of high physical activity, high need for thermoregulation (because of their lean body with low insulation) and high heat production in muscle tissues. To be able to survive, newborn piglets may rely upon three different sources of energy, namely, glycogen, colostrum and transient milk, which orchestrate to cover their energy requirements. Piglets are born with limited amounts of energy in glycogen depots in the liver and muscle tissues and these depots are sufficient for normal activity for ∼16 h. Intake and oxidation of fat and lactose from colostrum must supply sufficient amount of energy to cover at least another 18 h until transient milk becomes available in the sow udder ∼34 h after the first piglet is born. Selection for large litters during the last two decades has challenged piglets even further during the critical neonatal phase because the selection programs indirectly decreased birth weight of piglets and because increased litter size has increased the competition between littermates. Different attempts have been made to increase the short-term survival of piglets, that is, survival until day 3 of lactation, by focusing on improving transfer of vital maternal energy to the offspring, either in utero or via mammary secretions. Thus, the present review addresses how sow nutrition in late gestation may favor survival of newborn piglets by increasing glycogen depots, improving colostrum yield or colostrum composition, or by increasing production of transient milk.